2021
DOI: 10.1108/tqm-09-2020-0207
|View full text |Cite
|
Sign up to set email alerts
|

Improving performance of the hospitalization process by applying the principles of Lean Thinking

Abstract: PurposeThe goal was to improve the quality of the hospitalization process and the management of patients, allowing the reduction of costs and the minimization of the preoperative Length of Hospital Stay (LOS).Design/methodology/approachThe methodology used to improve the quality of the hospitalization process and patient management was Lean Thinking. Therefore, the Lean tools (Value stream map and Ishikawa diagram) were used to identify waste and inefficiencies, improving the process with the implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 73 publications
0
14
0
2
Order By: Relevance
“…The investigations and the applications involving lean practices and BPM have already been carried out in the healthcare (Ferreira et al , 2018; Fiorillo et al , 2021) and transport sectors (Navarro, 2021) and also in universities (Hess and Benjamin, 2015). Van Assen (2018) found that lean practices are positively related to process improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The investigations and the applications involving lean practices and BPM have already been carried out in the healthcare (Ferreira et al , 2018; Fiorillo et al , 2021) and transport sectors (Navarro, 2021) and also in universities (Hess and Benjamin, 2015). Van Assen (2018) found that lean practices are positively related to process improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Schymik et al (2007) describe that it is through effectiveness that success of the process is guaranteed because it makes it possible to analyze the best and most successful processes, those that bring more satisfaction to the client and with relatively lower costs and wastes. Those aspects are very close aligned to the principles of the Lean management system, which involves many tools and methods to combating waste and continuously obtaining effectiveness (Fiorillo Sorrentino et al, 2021), what provide the support to the development of the hypotheses and conceptual model of this research.…”
Section: Process Effectivenessmentioning
confidence: 79%
“…This practice is very well aligned to the pursuit of making organizational activities more effective, since it involves internal and external processes, management or operational improvements, and low or high levels to optimize organizational activities, redraw flows, reduce waste, and generate lower costs (Fiorillo et al, 2021; Klein et al, 2021a; O’Reilly et al, 2019). By continuously improving daily tasks, processes become “clearer” and more effective and the achieving of greater organizational effectiveness with less resources is allowed (Rymaszewska, 2017).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In Kang and Manyonge's (2014) understanding, the primary objective of the Lean approach is to remove unnecessary steps from processes and procedures that do not add value to students, professors or employees (staff), which generate waste like unnecessary or duplication of information, unclear procedures, multiple approvals, overlapping course modules, pending decisions, data entry errors, etc. Identifying inefficiencies of a given process and its related wastes improve the organization's performance (Fiorillo et al, 2021). So, H3.…”
Section: Lean Management Practices In Heismentioning
confidence: 99%